Snooping Job Related Organizational Stress of Selected Faculty Members in Higher Education Institutions - P. Dueñas, Mary Joy (International Journal of Scientific Research and Management (IJSRM), 2023)
This study was conducted to determine the organizational stress of selected faculty members in higher education institutions. Using descriptive research designs, the study involved 256 selected full time regular faculty members in selected private and public colleges and universities in Negros. The survey questionnaire consisted of two parts: the demographic profile of the respondents and the level of stress mechanisms taken form COPE instrument by Carver (2013). Statistical tools included frequency counts, percentage distribution, mean ratings and standard deviation. Most faculty members belonged to age bracket of 39–47 years and were considered as middle adults. These are faculty members who had been in the institution for 1– 8 years. The majority of them were male and married that are caught in the midst of all these responsibilities from work and family and most of them were instructors. Among the organizational stressors, nature of work obtained the highest mean score and interpreted as moderately stressed as experienced by faculty members. Relationship with supervisors ranked second with the mean score of 2.56 interpreted as moderately stressed; co-curricular activities had a mean score of 2.50 interpreted as moderately stressed. Furthermore, time spent in school obtained a mean score of 2.28 interpreted as slightly stressed; relationship with the students got a mean score of 2.26 interpreted as slightly stressed and relationship with peers, ranked lowest with a mean score of 1.80 interpreted as slightly stressed.  Taken all together, the survey obtained a mean of 2.36, which is interpreted as slightly stress. Based on the results of the study, the following initiatives to mitigate the effect of stress are proper delegation of work assignment and effective stress management program with the support from school administration to make the faculty members feel that they are valued and taking care of.